11‐5: Late‐News Paper: High PPI Micro LED Display for Small and Medium Size. Issue 1 (29th May 2019) - Nakamitsu, Sho; Ito, Hiroaki; Suzuki, Takanobu; Nishide, Masahiko; Imaizumi, Kunio; Yamanoguchi, Katsumi; Rahadian, Fanny; Aoki, Katsumi; Matsuda, Seiji; Yokoyama, Ryoichi
Abstract : Our Micro LED Display achieved PPI the best in class based on LTPS display technologies, such as circuit design on a glass substrate, micro‐fabrication technology, and multi‐layer process. A full color display is realized with rich color reproduction by controlling each independent LED chip of RGB in accordance with chip characteristics.